The status of foreign trades under globalization in developing and developed countries with Turkey - (:unkn) unknown (IGI Global, 2018)
In Turkey, the volume of foreign trade, which was very small in the first years of the republic, raised due to the increasing population and the reviving economy. Imports and exports for Turkey, the proportion of equipment, investment goods, and raw materials that would have been used for industrialization has increased. Another type of trade that is desired to be implemented in Turkey in recent years is free trade. The implementations for free trade also bring the question together with themselves. Does globalization always affect developing countries in a positive correlation with their economies? The data taken from KOF Index of Globalization from ETH Zurich are going to be used to see the relationship with the data coming from imports and exports. Then for all developing countries a classification study is done and the relation of developing countries and Turkey is examined. The purpose of the chapter is to examine the number of imports and exports due to globalization indexes to understand the real impact and the direction of globalization from the perspective of Turkey. © 2018, IGI Global.